2018
DOI: 10.5812/jhealthscope.65472
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Framework for “Iranian Pay for Performance” Program for Non-Medical Workforce in Hospitals

Abstract: Introduction: Various pay for performance (PFP) models have been used for different purposes in many countries. The present study aimed to investigate the general framework and feasibility of the PFP program that was implemented in Iran (IR-PFP). Methodology: In 2016, a document analysis was performed to achieve the original framework, and to evaluate its validity with the help of 2 expert panels, and both phases were managed using a four-stage Hermeneutic cycle. Findings:The results of reviewing the documenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…• Considering the quantity and quality of staff performance in merit pays according to the type of activity and expanding the motivation and commitment of the hospital management team for the qualitative and quantitative growth of medical services (11).…”
Section: -1: Pay For Performance In Iranmentioning
confidence: 99%
“…• Considering the quantity and quality of staff performance in merit pays according to the type of activity and expanding the motivation and commitment of the hospital management team for the qualitative and quantitative growth of medical services (11).…”
Section: -1: Pay For Performance In Iranmentioning
confidence: 99%
“…Proper salaries are one of the main strategies to attract and retain the workforce [ 50 ]. Payments in the Iranian health system to non-medical workforces are based on the combination of fixed salaries and performance-based payments, and nurses cannot obtain additional incomes through the provision of private services in government-run healthcare settings [ 51 ]. Studies in Iran have shown that the bulk of the healthcare sector’s expenditures in all healthcare settings is mainly dedicated to physicians [ 50 ].…”
Section: Nursing Profession In Iranmentioning
confidence: 99%
“…Hence, to control resources, insurance organizations use various methods to control and assess the behavior of healthcare providers and patients covered by them (8)(9)(10). One of the methods to control the behavior of healthcare providers is the different ways of payments to healthcare providers that are calculated differently according to provider performance, type of department and department income (11).…”
Section: Iran's Health System Has Experienced Various Reformsmentioning
confidence: 99%